Lexical-semantic test in patients with aphasia: a case study - Esther, Tuin
This is a small neuropsycholinguistics study on 4 aphasic patients. This preliminary study was conducted to explore the residual ability of patients with aphasia in reading and comprehending concrete nouns. The study was conducted on 2 female and 2 male subjects, aged 15 to 49 years old who exhibited aphasia following stroke with time of post-onset range from 12 days to 8 months and 25 days. All the subjects were required to read 50 concrete nouns and identify the picture of it as lexical-semantic test. The subjects performances were analyzed and discussed based on the variables that influenced the results. The result showed that NSF who was aged 15 years 5 months old prior to brain hemorrhage was able to read 98% of the words and identify 90% of the pictures. WZM who was tested after 8 months 25 days of stroke post-onset prior to testing was able to read 54% of concrete nouns and identify 94% of the pictures. MJS who was suffered from multifocal infarct bilateral frontal lobes (left middle cerebral territory) with hemorrhagic transformations scored unable to read but able to access the lexical representations 30% of the stimulus. Meanwhile, the newly attacked stroke, AMZ who was suffered aphasia almost 12 days prior to testing, considered as the lowest scorer in lexical-semantic test. From this study, the factors that distinguished one patient from another are age at the time of onset and different site of lesion.